The Soft Touch. - Wilson, Keith (Geographical (Geographical Magazine Ltd.), 2018)
The article offers information about the art and imaging techniques of geophotography, particularly on the concept of soft focus photography. Other topics being presented include creative and experimental methods of exposure as well as photographing moving subjects and making one sharply focused exposure of the subject such as a wildflower.